Crippling Connectivity : Unveiling the Network Disruption Potential of Vehicular Rogue Access Points - Dr. Kashyap C. Patel; Dr. Sachin A. Goswami; Dr. Saurabh A. Dave; Ajaykumar Patel (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Vehicular Networks have transformed modern transportation by facilitating communication between vehicles (V2V) and between vehicles and infrastructure (V2I). Nevertheless, this technical progress brings forth new security risks, including Vehicular Rogue Access Points (VRAPs), which have the potential to disrupt network connectivity and jeopardize the integrity of vehicular networks. This research investigates the menace presented by VRAPs, analyzing their capacity to cause significant disruptions to computer networks. We conduct a thorough analysis to emphasize the methods by which VRAPs can be utilized, the many types of assaults they can enable, and the subsequent consequences for the security of vehicular networks. The results of our research highlight the immediate requirement for strong security measures to protect vehicular network from these types of risks.